The Implementation of Internship Policy in Strengthening Vocational Students’ Skills and Competence to Meet the Demands of the Labor Market - Wati, Karsiyah; Trihantoyo, Syunu; Riyanto, Yatim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to identify the implementation of soft skills and hard skills, explore strategies for developing hard skills, and analyze entrepreneurial independence among vocational students. Using a qualitative approach, data were collected through interviews and observations, then analyzed descriptively through data reduction, presentation, and verification. The results show that soft skills are internalized through workplace culture programs emphasizing ethics, communication, and adaptability, supported by mentoring and reflection activities. Hard skills are applied in alignment with industry needs through curriculum synchronization, hands-on practice, and skill-based projects, ensuring professional competence. Development of hard skills is strengthened through internships, external training, and peer teaching, with success assessed from product quality, innovation, and relevance to market demand. Entrepreneurial independence is fostered through motivation, alumni inspiration, and the Teaching Factory program that integrates learning with real business experiences. Internships also help students interact directly with customers and handle business challenges, while sustainability is maintained through product management and freelance opportunities. Overall, the implementation of internship-based learning effectively enhances vocational students’ technical and non-technical competencies, enabling them to adapt, innovate, and compete in the dynamic job market.